MEF2C: A Novel Transcription Factor Implicated in Human Malignant Tumors - Pan, Yining; Li, Jiayi; Liu, Haoran; Ma, Jiayi; Wang, Dongshuo; Li, Xiaolan; Yuan, Chengfu (Current Topics in Medicinal Chemistry, 2025)
<span class=
Keywords: tumorigenesis